1991
DOI: 10.5014/ajot.45.3.214
|View full text |Cite
|
Sign up to set email alerts
|

Rigor in Qualitative Research: The Assessment of Trustworthiness

Abstract: Despite a growing interest in qualitative research in occupational therapy, little attention has been placed on establishing its rigor. This article presents one model that can be used for the assessment of trustworthiness or merit of qualitative inquiry. Guba's (1981) model describes four general criteria for evaluation of research and then defines each from both a quantitative and a qualitative perspective. Several strategies for the achievement of rigor in qualitative research useful for both researchers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
2,035
0
83

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,596 publications
(2,129 citation statements)
references
References 12 publications
11
2,035
0
83
Order By: Relevance
“…24 Therefore, as part of the process of the meta-synthesis, the quality of relevant studies was evaluated using predetermined criteria. 21,30 Krefting 42 observed that 'too frequently, qualitative research is evaluated against criteria appropriate to quantitative research and is found to be lacking'. This is not due to an inherent inadequacy, but rather to the inappropriate imposition of criteria developed for a different form of inquiry.…”
Section: Methodsmentioning
confidence: 99%
“…24 Therefore, as part of the process of the meta-synthesis, the quality of relevant studies was evaluated using predetermined criteria. 21,30 Krefting 42 observed that 'too frequently, qualitative research is evaluated against criteria appropriate to quantitative research and is found to be lacking'. This is not due to an inherent inadequacy, but rather to the inappropriate imposition of criteria developed for a different form of inquiry.…”
Section: Methodsmentioning
confidence: 99%
“…Codes were compared and disagreements were discussed. Peer examination guards against bias and enhances the robustness of the findings (Burnard 1991, Krefting 1991. Codes were collapsed by grouping together similar codes and coding was refined until the main themes emerged.…”
Section: Resultsmentioning
confidence: 99%
“…This study used several methods to enhance rigour. First, the participants were provided with transcribed interviews to check, thereby enhancing the accuracy of the information (Krefting 1991). Second, transcripts were coded independently by three researchers and themes were developed by subsequent discussion, which improved the reliability of the analysis (Mays and Pope 2000).…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Another method of increasing credibility is through peer examination which involves the researcher discussing the research process and findings with people who have experience with qualitative methods (Beck, 1993;Krefting, 1991). In this study, my thesis supervisory committee was composed of two faculty members from the School of Nursing, Memorial University of Newfoundland.…”
Section: Credibility Of Findingsmentioning
confidence: 99%